Patient-Centered Care in Small Primary Care Practices in New York City: Recognition Versus Reality - Margaret M. Paul; Stephanie L. Albert; Tod Mijanovich; Sarah C. Shih; Carolyn A. Berry (SAGE Publishing, 2017)
Background: The Primary Care Information Project (PCIP) is a program administered by the New York City Department of Health and Mental Hygiene to help primary care providers adopt a fully functional electronic health record (EHR) and focus on population health. PCIP also offers practices assistance with the National Committee for Quality Assurance (NCQA) patient-centered medical home (PCMH) recognition application. The objectives of this study were to assess the presence of key dimensions of PCMH among PCIP practices with 5 or fewer providers and to determine whether and to what extent NCQA recognition was related to the presence of these dimensions. Methods: Analyses relied on data collected from a comprehensive practice assessment survey of PCIP practices administered in summer 2012. The survey was developed to assess discrete dimensions of the PCMH model and other practice characteristics. The study population includes practices for which survey results were available among PCIP practices with 5 or fewer providers (63% response rate; n = 83). Results: At the time of survey, 57% of practices had received some level of NCQA recognition (n = 47). Practices with recognition scored significantly higher on several dimensions, including whole person orientation, team-based care, care coordination and integration, and quality and safety. Conclusions: Results indicate that very small urban practices in New York City are implementing many key features of PCMH. In general, practices with NCQA recognition scored higher on PCMH constructs and domains relative to practices without recognition; however, there is room for improvement on construct and domain scores in both groups.